2017
DOI: 10.1111/ajt.14441
|View full text |Cite
|
Sign up to set email alerts
|

PROviding Better ACcess To ORgans: A comprehensive overview of organ-access initiatives from the ASTS PROACTOR Task Force

Abstract: The American Society of Transplant Surgeons (ASTS) PROviding better Access To Organs (PROACTOR) Task Force was created to inform ongoing ASTS organ access efforts. Task force members were charged with comprehensively cataloguing current organ access activities and organizing them according to stakeholder type. This white paper summarizes the task force findings and makes recommendations for future ASTS organ access initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…[24][25][26] Experts have repeatedly recommended utilizing all deceased donor kidneys that are acceptable for transplantation. 27,28 However, US transplant programs are less likely to use a wider range of deceased donors for transplantation compared to other countries. For instance, estimates suggest that 62% of the kidneys discarded annually in the US would have been transplantable in France based on their characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Experts have repeatedly recommended utilizing all deceased donor kidneys that are acceptable for transplantation. 27,28 However, US transplant programs are less likely to use a wider range of deceased donors for transplantation compared to other countries. For instance, estimates suggest that 62% of the kidneys discarded annually in the US would have been transplantable in France based on their characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Experts have repeatedly recommended utilizing all deceased donor kidneys that are acceptable for transplantation 27,28 . However, US transplant programs are less likely to use a wider range of deceased donors for transplantation compared to other countries.…”
Section: Discussionmentioning
confidence: 99%
“…4 There is a paucity of data on the effect of a designated OPO procurement surgeon; however, one study from Europe has suggested that professionalization of procurements can lead to more organs available for transplantation and fewer surgical injuries. 5 OPOs have employed other novel methods to change the traditional model of organ procurement, such as utilizing an OPO procurement center, 6 which has been shown to decrease cost and increase organs procured, 7 and also prevent burnout and promote safety in transplantation. 8 The role of the OPO surgeon is not to entirely replace institutional procurement teams but rather to assist in the procurement and placement of organs.…”
Section: Introductionmentioning
confidence: 99%
“…OPOs have employed other novel methods to change the traditional model of organ procurement, such as utilizing an OPO procurement center, 6 which has been shown to decrease cost and increase organs procured, 7 and also prevent burnout and promote safety in transplantation 8 . The role of the OPO surgeon is not to entirely replace institutional procurement teams but rather to assist in the procurement and placement of organs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is undeniable the efforts countries have made to increase the number of donors and to reduce the gap between demand and supply of organs. In the United States, for example, the American Society of Transplant Surgeons (ASTS) envisioned ending organ shortages by increasing post-mortem donations, living donations, and better utilization of organs (Hobeika et al 2017). It is paramount to face ODTSC challenges and it equally important to improve its performance.…”
Section: Introductionmentioning
confidence: 99%